The Role of Brand Satisfaction in Mediating the Effect of Brand Experience and Brand Image on Brand Loyalty - Ari Anggarani Winadi Prasetyoning Tyas; Irvan Bagastoro Sulistyo (Institut Bisnis Nusantara, 2025)
Increasingly fierce competition in the smartphone industry requires companies to build brand loyalty through strong brand experience and brand image. This study aims to determine the influence of brand experience and brand image on brand loyalty with brand satisfaction as a mediator among iPhone users. This study uses a quantitative approach with a survey method, distributing questionnaires to 145 iPhone users in Jakarta and Bekasi. The sample size of 145 respondents is based on the minimum sample size rule proposed by Hair, which states that the minimum sample size is calculated as the number of questionnaire items multiplied by 5. Data analysis was conducted using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results indicate that brand experience and brand image have a positive and significant effect on brand loyalty, but brand satisfaction does not significantly influence brand loyalty and does not mediate the relationship between brand experience and brand image on brand loyalty. These findings indicate that iPhone users' loyalty is more influenced by direct experience and perception of the brand, rather than emotional satisfaction alone. Therefore, companies need to maintain the quality of brand experience and strengthen an exclusive and innovative brand image to sustainably enhance consumer loyalty, particularly among the Gen Z and millennial segments, who constitute the majority of users.